Does local government tax competition promote industrial transformation and upgrading? - Yuxin Meng; Xiaodong Yang; Chunji Zheng (PLoS ONE, 2025)
Promoting industrial transformation and upgrading (ITU) is the vital driving force for achieving high-quality economic development. This paper systematically interprets the theoretical mechanism of the impact of local government tax competition on ITU from a theoretical perspective. On this basis, a two-way fixed effects model is used to examine the impact of local government tax competition on ITU, the transmission mechanism, and the moderating effect of technological innovation. The study finds an inverted “U-shaped” relationship between local government tax competition and ITU, with tax structure, income distribution, and industrial agglomeration playing a non-linear mediating role. Improvements in technological innovation will reinforce the inverted “U-shaped” relationship between local government tax competition and ITU. The inverted “U-shaped” impact of local government tax competition on ITU is more pronounced in cities without economic growth targets, cities in eastern China, economically developed cities, and cities with weak tax enforcement capabilities. The research findings provide theoretical support and decision-making references for optimizing local tax policies and promoting high-quality economic development.